La publicidad de las tiendas por departamentos de la ciudad de México en los albores del siglo XX - Sánchez Parra, Cristina (El Colegio de México, A.C., 2020)
This article explores the different advertising strategies utilized by department stores in Mexico City at the end of the 19th Century and the beginning of the 20th. Its premise is that these businesses established a new tradition of consumption by introducing fixed prices, exhibiting their merchandise in their storefronts and instituting a new advertising language. All of these characteristics marked the appearance of new subjectivities of urban consumption. Through an analysis of official municipal documents and the contemporary press, this article postulates that these transformations in advertising messaging can be seen as part of the process of Porfirian modernization, which was modeled after developments in cities such as London and Paris. The image of Europe was a constant reference that allows us to identify external influences, as well as those phenomena that were particular to Mexico City at the turn of the century.